Ag Journalism (1959)
Agricultural Journalism department faculty in 1959-1960. Left to right: John Healey, Clyde Hostetter (acting department head), Vincent Gates, Loren Nicholson. Not pictured is Douglass Miller. A photo taken at the same photoshoot is used in the 1960 El Rodeo Yearbook.